Planning Head and Neck radiotherapy in contrast CT: viability for AAA and AcurosXB - Nardi, Paloma Natali; Beraldo Oliveira, Bruno; de Faria Morato, Leonardo; Carmello Guimarães, Lucas Francisco; Altei, Wanessa Fernanda; Giglioli, Milena (Revista Brasileira de Física Médica, 2022)
Background and purpose: many radiotherapy services execute two computed tomography (CT) scans for the treatment of head and neck (H&N) tumors: with (contrast CT) or without contrast (non-contrast CT), for dose calculation and target volume delineation, respectively. However, performing two CT scans brings problems such as unnecessary exposure of the patient to radiation and errors in CT images fusion. Therefore, the objective of this study was to verify the possibility of performing only the contrast CT as the routine for dose calculation with AAA and AcurosXB. Materials and methods: contrast and non-contrast CT scans from 77 patients were retrospectively analyzed and the Hounsfield Unit (HU) values ​​of the target volume and some organs at risk (as well as dosimetric values ​​were evaluated and compared. Statistical analysis was performed by calculating the intraclass correlation coefficient (ICC), assuming a significance level of 5%. Results: there is a correlation between the values ​​obtained for both HU and dosimetric data between the CT scans since the ICC was close to 1 and the p-value was lower than 0.05 for all cases. Conclusion: it is possible to perform only the contrast CT in the simulation routine for the treatment of patients with head and neck tumors. Keywords: Radiotherapy; Computed tomography; Contrast Agent; Dose Calculation; AAA; AcurosXB; VMAT; IMRT